Research and practices on open innovation: perspectives on SMEs - Rahman, Md. Hakikur (2011)
Innovation has become a recognized driver of economic prosperity of a country through sustained growth of its entrepreneurships. Moreover, recently coined term open innovation is increasingly taking a lead in enterprise management in terms of sustained profitability. Foci of researchers and practitioners are revolving around innovation methods, processes, and strategies. This chapter seeks to find out open innovation researches and practices that are being carried out circumscribing development of small and medium enterprises (SMEs) through a longitudinal study. Along this context the study is investigating into researches that are being carried out by leading researchers and research houses across the globe, and at the same time, it also investigates open innovation practices that are being carried out for the development of SMEs. Before its conclusion, the chapter attempts to develop a framework for future research practices.